2014
DOI: 10.1128/cvi.00221-14
|View full text |Cite
|
Sign up to set email alerts
|

Tonsils of the Soft Palate Do Not Mediate the Response of Pigs to Oral Vaccination with Heat-Inactivated Mycobacterium bovis

Abstract: f Mycobacterium bovis causes animal tuberculosis (TB) in cattle, humans, and other mammalian species, including pigs. The goal of this study was to experimentally assess the responses of pigs with and without a history of tonsillectomy to oral vaccination with heat-inactivated M. bovis and challenge with a virulent M. bovis field strain, to compare pig and wild boar responses using the same vaccination model as previously used in the Eurasian wild boar (Sus scrofa), to evaluate the use of several enzymelinked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(60 reference statements)
2
12
1
Order By: Relevance
“…In general, ELISA test sensitivity in piglets was lower than those reported in previous studies on wild boar of all ages (>70%; Lyashchenko et al, 2008) and in pigs (94%; Beltrán-Beck et al, 2014). In human TB, diagnosis in pediatric patients is also difficult by any available method and serology is not an exception.…”
Section: Discussioncontrasting
confidence: 76%
“…In general, ELISA test sensitivity in piglets was lower than those reported in previous studies on wild boar of all ages (>70%; Lyashchenko et al, 2008) and in pigs (94%; Beltrán-Beck et al, 2014). In human TB, diagnosis in pediatric patients is also difficult by any available method and serology is not an exception.…”
Section: Discussioncontrasting
confidence: 76%
“…This study demonstrates that the use of oral HI vaccine does not produce interference in diagnostic techniques used in TB eradication programs, as previously was observed in wild boar ( 20 ), pig ( 23 ), red deer ( 25 ), and cattle ( 26 ). The mechanism for this absence of interference has not been elucidated although it may be related to the different absorption routes or to the adjuvants used.…”
Section: Discussionsupporting
confidence: 75%
“…This limited sampling time schedule was due to these animals entering a second experimental phase where they were subsequently exposed to a group of TB-infected animals in order to continue with an efficacy study. Third, the age of vaccination with the HI vaccine differed among previous studies: red deer (adults), cattle (5–7 months), wild boar (3–4 months), and pigs (3–4 months); sampling schedule after vaccination was also different in these studies: red deer (months 7 and 12), cattle (weekly up to 8 weeks after vaccination), wild boar (day 60), and pigs (day 57) ( 20 , 23 26 ). Few studies in humans have focused on the role of vaccine administration-related parameters on vaccine efficacy, since factors as the number and interval between immunizations could trigger different immunological responses ( 40 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, we could not perform a bacterial culture of target tissues. The "Serum ELISA" used in our pilot study as a reference test has previously shown a sensitivity ranging from 86.4% (in natural wild boar infections) to 94.4% (in experimental wild boar infections, [44]), and a specificity of 100% [45]. Diagnostic accuracy may be underestimated when a reference standard with reduced sensitivity is used.…”
Section: Discussionmentioning
confidence: 98%